Different iPSC-derived neural stem cells shows various spectrums of spontaneous differentiation during long term cultivation - Galiakberova, Adelya Albertovna; Brovkina, Olga Igorevna; Kondratyev, Nikolay Vitalyevich; Artyuhov, Alexander Sergeevich; Momotyuk, Ekaterina Dmitrievna; Kulmukhametova, Olga Nikolaevna; Lagunin, Alexey Aleksandrovich; Shilov, Boris Vladimirovich; Zadorozhny, Anton Dmitrievich; Zakharov, Igor Sergeevitch; Okorokova, Larisa Sergeevna; Golimbet, Vera Evgenievna; et al. (Frontiers in Molecular Neuroscience, 2023)
Introduction Culturing of human neural stem cells (NSCs) derived from induced pluripotent stem cells (iPSC) is a promising area of research, as these cells have the potential to treat a wide range of neurological, neurodegenerative and psychiatric diseases. However, the development of optimal protocols for the production and long-term culturing of NSCs remains a challenge. One of the most important aspects of this problem is to determine the stability of NSCs during long-term in vitro passaging. To address this problem, our study was aimed at investigating the spontaneous differentiation profile in different iPSC-derived human NSCs cultures during long-term cultivation using. Methods Four different IPSC lines were used to generate NSC and spontaneously differentiated neural cultures using DUAL SMAD inhibition. These cells were analyzed at different passages using immunocytochemistry, qPCR, bulk transcriptomes and scRNA-seq. Results We found that various NSC lines generate significantly different spectrums of differentiated neural cells, which can also change significantly during long-term cultivation in vitro. Discussion Our results indicate that both internal (genetic and epigenetic) and external (conditions and duration of cultivation) factors influence the stability of NSCs. These results have important implications for the development of optimal NSCs culturing protocols and highlight the need to further investigate the factors influencing the stability of these cells in vitro.